Adaptive mechanochemical mechanisms of the nucleus during confined cell migration - Wenying Luo; Xindong Chen; Bo Li; Xi-Qiao Feng (Proceedings of the National Academy of Sciences, 2026)
Cell migration through spatially confined microenvironments occurs in many biological processes such as embryonic development, immune surveillance, and cancer metastasis. A major bottleneck during such migration is the nucleus, which acts not only as a rigid mechanical obstacle but also as a crucial mechanosensor that modulates downstream signaling pathways. However, it remains poorly understood how nuclear deformation and mechanosensation together regulate cell migration through confined spaces. Here, we propose a three-dimensional (3D) mechanochemical model of confined nuclear translocation that integrates nuclear deformation with deformation-induced calcium signaling and subsequent regulation of cytoskeletal contractility. We show that cells undergo adaptive nuclear deformation, including nuclear envelope elongation and 3D buckling, to efficiently navigate confinements of varying sizes. There exists a biphasic relation between nuclear velocity and confinement size, arising from the interplay between nuclear deformability and mechanosensitive feedback. We demonstrate that local nuclear envelope rupture can occur under large deformation, enabling nuclear translocation through extreme confinements, as observed in prior experiments. Furthermore, we elucidate the critical roles of chromatin organization in nuclear translocation. This work reveals key mechanochemical mechanisms driving confined cell migration and provides a theoretical framework for studying nuclear dynamics across physiological and pathological contexts.